WEB-BASED COFFEE SALES INFORMATION SYSTEM: (A Case Study Of Cerita Teras Coffee Shop) - Martin Alberto Barros De Araujo; Handoko (Infact: International Journal of Computers, 2026)
The rapid advancement of information technology has encouraged business owners to adopt digital systems to improve operational efficiency and service quality. Cerita Teras Coffee Shop still relied on a manual sales process, which often resulted in delayed transaction recording, difficulties in managing sales data, and less effective promotional activities. This study aims to design and implement a web-based coffee sales information system to improve transaction management and business operations. The research employed a developmental research method with a qualitative approach through observations and interviews to identify system requirements, followed by a quantitative approach to evaluate system performance. The research stages consisted of problem identification, data collection, requirement analysis, system design using the Waterfall method, system implementation, and testing through Black Box Testing and User Acceptance Testing (UAT). The developed system provides features for online ordering, product management, customer management, transaction processing, and automated sales reporting. The testing results indicate that all system functions operated successfully according to user requirements, while the User Acceptance Test achieved a satisfaction score of 90.91%, indicating that the system was highly accepted by users. Therefore, the proposed web-based sales information system effectively improves operational efficiency, facilitates transaction management, and enhances service quality at Cerita Teras Coffee Shop.